The impact of high-energy tailing in high-purity germanium gamma-ray spectrometry on the activity determination of 224Ra using the 241.0 keV emission. (March 2020) - Collins, S.M.; Shearman, R.; Ivanov, P.; Regan, P.H.
Abstract: High-energy tailing is an often-overlooked component in high-purity germanium gamma-ray spectrometry when performing the non-linear least squares fit of a full-energy peak. This component comes from the incomplete restoration of the baseline prior to the next pulse being processed and therefore is an issue of increased count rates. In the current work, the impact of this oversight is shown through the dynamics and decay characteristics of 224 Ra and its radioactive decay progeny. Multiple measurements of two samples, separated from the decay progeny and at differing activities, have been made. The results of full-energy peak fitting of the convoluted 238.6 keV and 241.0 keV full-energy peaks with and without the high energy tailing component are presented. Trends in the observed activity that approximate the ingrowth of 212 Pb have been observed where no high-energy tailing component is used, with maximum relative differences of 2% and 5% determined. Highlights: Error in the activity determination of 224 Ra due to high-energy tailing in gamma-ray spectrometry. Dynamics of 224 Ra and 212 Pb decay progeny ingrowth show evolution of error. Inclusion of high-energy tail in full-energy peak fitting resolves error.